Analisis Aspek-Aspek Keberhasilan Pembelajaran di Indonesia: Ditinjau dari Studi Observasi - Siregar, Deasy Yunita; Khairani, Lutfi Putri; Sabilla, Sonia; Yusriani, Yusriani; Siahaan, Rizki Putri Jasmine (EduInovasi: Journal of Basic Educational Studies, 2024)
The importance of this research lies in its contribution to the development of education policies, the formulation of more effective teaching strategies, and the guidance for education practitioners. With a better understanding of the factors influencing learning success, this research is expected to be a valuable guide in improving the quality of education in Indonesia to meet global demands and prepare future generations optimally. Observational analysis research is a research approach in which the researcher directly observes certain phenomena or events to gain a deeper understanding. In this context, "observational analysis" refers to the process of analyzing data obtained through direct observation. This method is usually used to explore in-depth information about behavior, interaction, or specific situations in a natural environment. Observational analysis research is often adopted in the fields of psychology, sociology, anthropology, and education (Moleong, 2010). Based on the background description of research related to the analysis of aspects of learning success in Indonesia through observational studies, it can be concluded that education in Indonesia faces complex and diverse challenges. Some obstacles, such as regional disparities, varying teacher quality, access to technology, and the role of parents in education, provide a context that requires serious attention.